Hiking in the landscape - the history of Europeans’ linkage to the landscape by hiking - Sales, Teresa Lúcio de (2018)
Since remote times, man has hiked in the landscape, establishing bonds of communication and interconnection between two or more points. Hiking along trails is the means of escape for man, causing changes in the landscape, and making known sites and places. In this paper, the history of the dynamics established between the act of walking and the landscape, along with the changes in society (predominantly since the 18th century), are presented. The existence of paths in nature is older than the very existence of mankind itself. The act of walking has always been associated with the history of man, who has hiked in the landscape looking for food, making pilgrimages, marketing products, promoting sustainable mobility, tourism and healthy recreation, and contributing to the improvement of the population’s quality of life. There is a special connection to the landscape by walking. The paths are areas marked by time and by society. They are understood as a way of reading the landscape. The act of walking is associated with an art in which the pleasure is rather in sensations of the soul [37]. When we walk, we are exclusively dependent on ourselves and completely free to observe and appreciate the landscape as best suits us and with a complete tranquility [30; 37]. Knowledge of the landscape involves movement, and the best form of perceiving and establishing a close relationship with that landscape is walking. Nowadays, there is a significant increase in adherence to outdoor activities, especially walking. People are looking for new ways of being in contact with nature. A restorative effect of nature on man is, indeed, one of the fundamental aspects of this increased demand, and people walk for different reasons. Hiking in the natural landscape assumes a great importance for the maintenance of a healthy body and mind. It is important that we develop future research to improve our knowledge not only about the influence of walking in the natural landscape, related especially to the benefits it has on man’s creativity, but also to improve the knowledge about how to combine modern life with the benefits of walking in nature.